CASTE ELEMENTS IN CATHOLIC COMMUNITY IN KERALA - Koilparampil, George (Journal of Dharma, 2001)
In this article we intend to make a general survey Of relevant literature on Caste Elements in the Catholic community. Rao Bahadur L.K. Ananthakrishna Ayyar’s study. ’Anthropology of the Syrian Christians" I is a comprehensive and reliable work on the manners and customs of the Syrians of Kerala. The field work was conducted as early as 1910 and the observations were first published as chapter 16 of the second volume of the "Cochin Tribes and Castes". 2 Anthropology of the Syrian Christians is an enlarged version of it with further additions under the. changing conditions.3 The volume begins with a preliminary historical account of the Syrian Church in Kerala in four chapters, and the remaining thirteen are devoted to the description of the manners and customs of the various sects.